Nie tylko zupka z muszek. Poetycki potencjał kulinariów w polskiej współczesnej poezji dziecięcej - Mazan-Mazurkiewicz, Alicja (Paidia i Literatura, 2022)
Alicja Mazan-Mazurkiewicz’s aim in this article is to show the richness and variety of poetical implementations of culinary themes in children’s poetry as represented by Joanna Kulmowa, Joanna Papuzińska, Zofia Beszczyńska, and Agnieszka Kuciak. Mazan-Mazurkiewicz wants to emphasise how a topic that is close to the child and somehow obvious makes it possible for the receiver to be themselves poetically creative and offers them an aesthetic experience as well as an initiation (often unconscious) into the processes of artistic creation, involving humour, metaphor, synaesthesia, and retardation.